Liver function parameters aspartate aminotransferase and total protein predict functional outcome in stroke patients with non-cardioembolism - Xie, Jiali; Zhu, Yinmeng; Pang, Chunyang; Gao, Lingfei; Yu, Huan; Lv, Wenjing; Zhang, Wanli; Deng, Binbin (Frontiers in Nutrition, 2022)
Stroke, classified as cardioembolism and non-cardioembolism (non-CE), entails a large socioeconomic burden on the elderly. The morbidity and mortality of non-CE are high, whereas studies concerning prognostic factors impacting function outcome remain underdeveloped and understudied. Liver function parameters are convenient approaches to predicting prognosis in cardiovascular diseases, but their clinical significance has not been well characterized in stroke, especially in non-CE. In our study, a total of 576 patients with non-CE at 1 year of follow-up were enrolled in a cohort from a consecutive hospital-based stroke registry, with randomly 387 patients as the development cohort and 189 patients as the validation cohort. The univariate and multivariate analyses revealed the following novel findings: (i) The incidence of unfavorable functional outcomes after non-CE was significantly greater (p < 0.01) in patients with higher age, aspartate aminotransferase (AST), the National Institutes of Health Stroke Scale (NIHSS) score, and depressed total protein (TP); (ii) We established a novel model and nomogram to predict stroke prognosis, in addition to the known factors (age and the NIHSS score). The levels of AST and TP were independently correlated with the incidence of unfavorable outcomes [AST: odds ratio (OR) = 1.026, 95% CI (1.002–1.050); TP: OR = 0.944, 95% CI (0.899–0.991)]; (iii) The results persisted in further subgroup analysis stratified by age, gender, the NIHSS score, and other prespecified factors, especially in males 60 years or older. Overall, this study demonstrates that hepatic parameters (AST and TP) after non-CE are considered to be associated with functional outcomes at 1-year follow-up, especially in males aged ≥ 60 years.